INTERNATIONAL CRISES AND DEVELOPING ECONOMIES: LINKAGES AND RECENT EXPERIENCES†. (November 2013) - Amann, Edmund; Lawson, David; Lawson, David; Amann, Edmund
Abstract This article provides the theoretical and empirical context to the papers contained in this special issue. We provide background on the recent developed country financial crisis and perspective via a review of prior shocks and crises. The paper then considers the transmission mechanisms through which economic crises can affect economies and individuals in the developing world. The linkages centre on trade, capital flows and remittances. This section also critically surveys the literature concerning the macroeconomic and microeconomic impact of such crises on developing countries. Finally, we review the papers that comprise the special issue, before providing some policy conclusions. Copyright © 2013 John Wiley & Sons, Ltd.